2007
DOI: 10.5688/aj710112
|View full text |Cite
|
Sign up to set email alerts
|

An Online Debate Series for First-Year Pharmacy Students

Abstract: Objectives. This article describes an online debate series that was developed as a new component to an introductory core course for first-professional year pharmacy students. Objectives were to facilitate the group process, introduce controversial issues related to the US healthcare system, improve critical thinking and communication skills, enable students' ability to analyze and evaluate evidence, help develop skills in formulating written arguments, and encourage tolerance of diverse points of view. Design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 13 publications
0
47
0
2
Order By: Relevance
“…Although debating is not commonly reported in internal medicine residency or subspecialty fellowship training, other health-related training programs such as nursing, dental and pharmacy have utilized this teaching tool for educating their trainees. [5][6][7][8] Critical, reflective thinking is an essential element in patient care and other core competencies of postgraduate medical training. Debating is one such tool that may enhance critical thinking and communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Although debating is not commonly reported in internal medicine residency or subspecialty fellowship training, other health-related training programs such as nursing, dental and pharmacy have utilized this teaching tool for educating their trainees. [5][6][7][8] Critical, reflective thinking is an essential element in patient care and other core competencies of postgraduate medical training. Debating is one such tool that may enhance critical thinking and communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with other studies in professional programs that have shown debates cultivate skills such as communication, decisionmaking, and problem-solving. [8][9][10][11][12] However, students could have developed improvement in these skills outside the debate series. While the influence of other courses on skill development was inevitable, students were able to demonstrate certain skills during debate days.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 There are a few examples in the literature describing the use of debates in pharmacy curricula. [9][10][11] All of these examples have used debates in practice-related courses on the health system, legislation, and regulatory issues. One example included the use of debates in a pharmacokinetics course.…”
Section: Introductionmentioning
confidence: 99%